Pembelajaran Kiai Kholil Bangkalan dalam Analisis Teori Pembelajaran Humanistik - Lailatul Yusro; Nurus Sa’adah; Khairul Umam (NUMADURA: Journal of Islamic Studies, Social, and Humanities, 2024)
Among the various kinds of learning theories, humanistic learning theory is a learning theory with an approach that humanizes humans to make students become fully human. Kiai Kholil Bangkalan is an Islamic figure that most of his students have succeeded in becoming human beings in various social spaces. This is interesting to see from a humanistic perspective. Therefore this research aims to look at the learning implemented by Kiai Kholil from the perspective of humanistic theory using a qualitative literature review. We collected various literature related to humanistic learning and the learning applied by Kiai Kholil. From that various literatures, it was found that humanistic learning regardless of the originators is essentially a learning philosophy that pays great attention to the uniqueness of students so that human values ​​in students are cared for and developed according to their own uniqueness, therefore the application of humanistic learning is able to be entered in various spaces as long as it contains that values. In the learning system implemented by Kiai Kholil, these humanistic values​​ are indeed implemented, starting from classroom learning, sorogan, to indirect learning in the form of his treatment to the students is  different its called isyarah.